Effects of Intergroup Contact in an Official Bilingual Language Teaching Context on Mutual Stereotypes - Ngum, Melvis; Evani, Evani; Neba, Ayu'nwi (American Journal of Literature Studies, 2023)
Purpose: This paper reports findings of an investigation of the effects of intergroup contact in a bilingual language teaching context on stereotypes of each group towards each other. The pre and post intergroup contact attitudes of Cameroonian Anglophone Bilingual Teachers (ABT) and those of Francophone Bilingual Teachers (FBT) towards each other were determined and compared. Methodology: A mixed method research design that relied on a two-phase explanatory sequential strategy was employed to collect the data. It comprised an anonymous self-report survey of 97 bilingual teachers and a follow-up interview of 6 of these teachers. Descriptive statistics were used to analyze the quantitative data and content analysis was used to explore the textual data. Findings: The study revealed that while ABT indicated negative attitudes towards FBT, prior to starting their training, FBT on their part, expressed positive considerations of Anglophones (they saw them as polite, hospitable and hardworking people). In the end, ABT moved from seeing FBT as arrogant to calling them simple and assiduous learners. Nevertheless, they scorned the FBT's insolence. The contact reinforced FBT's prior training positive attitudes towards ABT whom they found to be friendly, convivial and courteous. Recommendations: The study concludes that intergroup contact positively influenced ABT attitudes towards FBT, while FBT maintained their pre-training positive attitudes towards ABT. Intergroup contact in an official bilingual teacher training classroom, therefore, can be a fertile ground for the elimination of stereotypes and promotion of the spirit of living together.